THE SOUTH CHINA SEA AS A FROZEN CONFLICT IN THE INDO-PACIFIC - Stanković, Đurđica (Political Review, 2023)
Territorial disputes in the Indo-Pacific pose challenges to interstate relations, both the region's countries and the United States. Although they are not part of the Indo-Pacific region, the role of the US is imposing, often influencing the dynamics of disputes and relations between states. The subject of this paper is the analysis of territorial and maritime disputes in the South China Sea. The research aims to analyze the geostrategic, trade, and economic potential of the South China Sea, but also to highlight the danger of the frozen conflict that exists in the Indo-Pacific. The main research question to which this paper attempts to offer an answer is: Why is the South China Sea important, and whether conflicts at sea threaten to lead the world into a new uncertain crisis? The author concludes that the problem of territorial disputes in the South China Sea is not only a regional but par excellence an international problem that poses a serious challenge and threat to world order and global security. The theoretical framework used in the research is based on the analysis of maritime geopolitics and power relations of states through the prism of Mahan's geopolitical theory of naval power. The paper uses a contextual approach, a historical-comparative method, and a method of document content analysis.
Keywords: South China Sea; Indo-Pacific; Law of the Sea; USA; PRC